How do Brazilian Software Engineering Researchers Perceive and Practice Open Science? - OliveiraJr, Edson; Chavez, Christina von Flach G.; Cordeiro, André F. R.; Feitosa, Daniela (Anais do Workshop de Práticas de Ciência Aberta para Engenharia de Software (OpenScienSE); 2021: Anais do I Workshop de Práticas de Ciência Aberta para Engenharia de Software, 2021)
With the wide popularization and increasing adoption of Open Science, most scientific research areas have discussed its benefits to the overall society represented by any citizen. The openness process aims at promoting free availability of such researches, thus directly impacting scientific evolution. Researchers are encouraged to make scientific research artifacts open for every citizen. In the Software Engineering area we are currently experiencing international Open Science initiatives, such as the ICSE Rose Festival, the ESEM Open Science policies, and the Empirical Software Engineering journal Open Science initiative. However, a little is known about Open Science in the Brazilian Software Engineering community. Therefore, in this paper, we present and discuss the results of a survey on how do our software engineering community perceive and practice Open Science.